2016
DOI: 10.1177/1687814016671248
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of an instantaneous-heating air source heat pump water heater with a temperature stratified water tank

Abstract: An instantaneous-heating air source heat pump water heater with a temperature stratified water tank was put forward. The instantaneous-heating air source heat pump water heater was designed to produce hot water instantly by three modes, namely condenser heating, water tank heating and condenser-water tank joint heating. The heating mode is chosen as condenser heating when the ambient temperature is above 20°C (including 20°C) and is chosen as condenserwater tank joint heating below 20°C. A 3HP instantaneous-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These results could represent HPWH performance trends when coupled with a water-based solar collector to preheat the inlet water if the electric source in the study were replaced with a solar collector. The research by Bursill et al also showed an increase in performance of HPWH systems as the HPWH water temperature set point decreases, which is representative of other research in the field [16].…”
Section: Heat Pump Water Heaterssupporting
confidence: 54%
See 2 more Smart Citations
“…These results could represent HPWH performance trends when coupled with a water-based solar collector to preheat the inlet water if the electric source in the study were replaced with a solar collector. The research by Bursill et al also showed an increase in performance of HPWH systems as the HPWH water temperature set point decreases, which is representative of other research in the field [16].…”
Section: Heat Pump Water Heaterssupporting
confidence: 54%
“…However, a lower limit on the storage tank temperature of 49⁰C is required by the Canadian government to prevent growth of legionella bacteria. Lei et al [16] conducted experiments on an instantaneous HPWH and found that instantaneous HPWHs could achieve a COP as high as 12.6. This is because instantaneous water heaters are tankless which mitigates the risk of legionella, allowing low temperature setpoints to be used thus eliminating the energy consumption that tank water heaters use to reach higher temperatures.…”
Section: Heat Pump Water Heatersmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature stratification majorly determines the performance of a water-based thermal storage system. 2,3 The peak-load reduction effect of the storage tank can be further increased by precisely controlling the temperature stratification in the storage tank. The ideal stratification maximizes the energy efficiency of a heat storage tank.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al [19] designed and tested an instantaneous-heating air source heat pump water heater (IASHPWH) with a temperature stratified tank, using R410A refrigerant. The IASHPWH operated using three modes: condenser heating for a source temperature over 20 o C, water tank heating for a source temperature below 20 o C and condenser-water tank joint heating.…”
Section: Heat Pump Technologymentioning
confidence: 99%